Higgs and Coulomb branches from vertex operator algebras - Costello, Kevin; Creutzig, Thomas; Gaiotto, Davide (Journal of High Energy Physics, 2019)
We formulate a conjectural relation between the category of line defects in topologically twisted 3d N = 4 supersymmetric quantum field theories and categories of modules for Vertex Operator Algebras of boundary local operators for the theories. We test the conjecture in several examples and provide some partial proofs for standard classes of gauge theories.
CRIS-Team Scopus Importer:2024-06-24
Keywords: Conformal Field Theory; Supersymmetric Gauge Theory; Topological Field Theories